Navigating the Missteps: An In-Depth Critique of Albania's Sex Offender Registry - Adrian Leka; Brunilda Haxhiu (Journal of Systemics, Cybernetics and Informatics)

(untitled)
This article critically examines the legislative journey and implications of Albania's Sex Offender Registry Law 62/2023, shedding light on the disconnection between scientific research and public policy formulation. Tracing the historical origins of sex offender registries and contrasting various international models, the study underscores the lack of alignment between the approved law and established research findings. The article highlights the overestimation and misrepresentation of statistical data, the shortcomings in the legislative process, and the absence of a transparent, evidence-based approach. The law's failure to materialize the intended registry within the stipulated timeframe and the inherent limitations of the approved model further emphasize the challenges in creating effective legislation. The findings not only critique the flaws in Law 62/2023 but also reflect broader concerns about utilizing scientific research in shaping legal frameworks, underscoring the need for a more informed and evidence-driven approach to policymaking.